2020
DOI: 10.3390/molecules25112675
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineering of Cytochrome P450 OleTJE: How Does Substrate Positioning Affect the Product Distributions?

Abstract: The cytochromes P450 are versatile enzymes found in all forms of life. Most P450s use dioxygen on a heme center to activate substrates, but one class of P450s utilizes hydrogen peroxide instead. Within the class of P450 peroxygenases, the P450 OleTJE isozyme binds fatty acid substrates and converts them into a range of products through the α-hydroxylation, β-hydroxylation and decarboxylation of the substrate. The latter produces hydrocarbon products and hence can be used as biofuels. The origin of these produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 104 publications
(207 reference statements)
3
19
0
Order By: Relevance
“…The middle panel gives energies relative to 4 Re S1 in kcal mol −1 as obtained at the ∆E+ZPE level of theory. Transition state structures are shown on the side with bond lengths in angstroms and the imaginary frequency in the transition state in cm −1 .The transition states have typical features of OH rebound and desaturation barriers and match previous work on substrate hydroxylation and desaturation by P450 enzymes[36,38,[51][52][53][64][65][66][67][68][69]72,79,88,89]. The rebound transition state has a long C-O distance of 2.354 Å, although the imaginary frequency (i469 cm −1 ) is clearly a pure C-O stretch vibration.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…The middle panel gives energies relative to 4 Re S1 in kcal mol −1 as obtained at the ∆E+ZPE level of theory. Transition state structures are shown on the side with bond lengths in angstroms and the imaginary frequency in the transition state in cm −1 .The transition states have typical features of OH rebound and desaturation barriers and match previous work on substrate hydroxylation and desaturation by P450 enzymes[36,38,[51][52][53][64][65][66][67][68][69]72,79,88,89]. The rebound transition state has a long C-O distance of 2.354 Å, although the imaginary frequency (i469 cm −1 ) is clearly a pure C-O stretch vibration.…”
supporting
confidence: 71%
“…The substrate binding pocket contains the peptide dimers Leu 78 -Phe 79 and Arg 245 -Pro 246 as well as the side chains of residues Ile 170 and Phe 291 . A previous study used the same peptide and active site model but with hexanoate as substrate [38], whereby the model was validated against highlevel quantum mechanics/molecular mechanics (QM/MM) calculations [51,52] and large cluster models [53]. These studies found very good agreement of the calculations of energy landscapes for a reaction mechanism, as obtained with either cluster models or QM/MM.…”
Section: Resultsmentioning
confidence: 86%
“…To put these values in perspective, the C-O distances are longer than those reported for the rebound step in cycloheptatriene hydroxylation by an iron(IV)(oxo)(pentafluorophenyl-porphyrin) complex, which found doublet and quartet spin transition states with C-O distances of 1.831 and 2.053 Å. 65 Calculations for the small aliphatic substrates methane and propene and iron(IV)(oxo)(porphine) lead to much longer C-O distances of 2.556 and 2.427 Å, respectively, in the rebound transition states. 12 Long C-O distances were also found for the rebound transition states during methane hydroxylation by μ-nitrido-bridged diiron(IV)-oxo porphyrinoid complexes.…”
Section: Computational Studiesmentioning
confidence: 83%
“…68 Although the catalytic role of such an Fe-alkoxide species in aliphatic hydroxylation reaction, such as VioC catalyzed L-arginine hydroxylation, is still unclear, a similar species in the epoxidation reaction has long been proposed in experimental and computational studies on both heme dependent enzymes, [30][31][32][33][34][35][36]39 and heme and non-heme biomimetic model complexes. 37,38,45,[69][70][71][72][73][74] Yet, it is the first time that such a species is experimentally identified in an enzymatic epoxidation reaction. In addition, the Fe-alkoxide species has also been proposed as the key intermediate for aromatic hydroxylation catalyzed by non-heme iron enzymes.…”
Section: Crystallographic Characterizations Of the Asqj Catalyzed Epoxidationmentioning
confidence: 99%